ASSESSMENT OF PLACENTAL OXIDATIVE STRESS PARAMETERS IN PREECLAMPTIC AND NORMAL PREGNANT WOMEN - V, Kavitha; B, SRINIVAS; Mvln, Praveen Kumar; P, Shashikanth (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Oxidative stress occurs when cellular levels of reactive oxygen species exceed antioxidant capabilities and has been implicated in the pathogenesis of pre-eclampsia. In this study, we examined the tissue levels of endogenous antioxidant enzymes or proteins (superoxide dismutase [SOD], glutathione peroxidise, reduced glutathione, catalase, and thioredoxin) and the levels of lipid peroxides, protein carbonyls, hydrogen peroxide, and nitrosative biomarkers in the placental samples from normal and pre-eclamptic pregnancies. Results: Pre-eclamptic tissue homogenates demonstrated significantly increased levels of lipid peroxidation (21.61±0.18 vs. 5.695±0.46) and a trended increase in protein carbonyls (245.95±4.05 vs. 203.48±3.65) concentration when compared to controls. The levels and activities of the antioxidant proteins; SOD (365.2±2.915 vs. 205.6±3.76), thioredoxin (100.64±3.38 vs. 80.89±3.37), glutathione peroxidase (340.88±6.16 vs. 164.46±3.03), catalase (5.26±0.02 vs. 4.62±0.11), and reduced glutathione (46.99±0.508 vs. 28.19±0.178) were all found to be significantly reduced when comparing pre-eclamptic placental tissue homogenates to gestational age matched control placentae from non pre-eclamptic pregnancies. Conclusion: The results of this study demonstrate a decreased enzymatic antioxidant capacity and increased oxidation in placental tissue from preeclamptic women, which may contribute to the pathogenesis of this complex disorder. Keywords: Oxidative stress, Reactive oxygen species, Superoxide dismutase, Glutathione peroxidise, Reduced glutathione, Catalase, Thioredoxin, Lipid peroxides and protein carbonyls.